(3JMaI Phi GdCQH aj eTcd GdCSeGA hGdfSH aj VHW eG hbY aj GdehWC hGdUMjMjfs - (3eMehO Hf CMeO Hf eMeO GdgePGfj Gdajhej GdCUd, GdMehj, GdTGaYqj, CHh GdKfGA, fhQ GdOjf, GdeYQha HGHf nNpWjH GdnqOrgnTI,J (B834 (3g` s ((3eMeO Hf CMeO GdcQci s)
(3ChdgG (B:s
(3GdMeO ddg hGdTcQ dg s
(3eQJH Ydi MQha GdgLGAs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B162 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B148s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B82 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI HTjQ CZG (B((3CjhH(B) ((1)186) s
Keywords: (3GdJGQjNs